1991
DOI: 10.1007/bf02657533
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigations of β′ triacylglycerols: An x‐ray diffraction and microscopic study of twinned β′ crystals

Abstract: To reveal the structure ofβ′ triacylglycerols in detail, LML (C12C14C12) was purified by a zone‐melting procedure, and twinned crystals ofβ′ stable LML were obtained from a melt,β′ LML crystallizes in the monoclinic space group C2, with eight molecules in the unit cell. A powder X‐ray diffraction study of solid compounds of 1:1 mixtures of selected triacylglycerols led to the conclusion that the triacylglycerol molecules in theβ modification have a 1,2 chair‐conformation (i.e., the fatty acid chains on glycero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Birker et al (19) also reported cell parameters of β′-LML comparable to the parameters as determined in this study (Table 1). They also observed the Ic2a pseudosymmetry but concluded finally that the space group was C2.…”
Section: Determination Of Cell Parameters and Space Groupsupporting
confidence: 88%
See 1 more Smart Citation
“…Birker et al (19) also reported cell parameters of β′-LML comparable to the parameters as determined in this study (Table 1). They also observed the Ic2a pseudosymmetry but concluded finally that the space group was C2.…”
Section: Determination Of Cell Parameters and Space Groupsupporting
confidence: 88%
“…For β′-1,3-dihexadecanoyl-2-octadecanoyl-glycerol, or C 16 C 18 C 16 (β′-PSP) he suggested that the alternating tilt of chains will be realized (17) determined the unit-cell parameters and space group of β′-1,2,3-triundecanoyl-glycerol, or triundecanoin (β′-C 11 C 11 C 11 ) and postulated a similar alternating chain-tilt angle (τ) and the necessity of two molecules in the asymmetric unit (17,18). Birker et al (19) revealed from a single-crystal analysis the unit-cell parameters and space group of β′-1,3-didodecanoyl-2-tetradecanoyl-glycerol, or C 12 H 14 C 12 (β′-LML) and concluded LML to be monoclinic with space group C2, but exhibiting pseudo-orthorhombic symmetry. Based on this space group they assumed alternating tilts again and, moreover, the impossibility of straight LML molecules in the cell.…”
mentioning
confidence: 99%
“…Twinned crystals of/3' LML were grown as reported earlier (1). A TopoMetrix (Darmstadt, Germany) TMX 2000 Atomic Force/Lateral Force Microscope was used to probe the c surface structure of p' LML crystal.…”
Section: Methodsmentioning
confidence: 99%
“…A crystallographic investigation of twinned crystals of the f3' modification of the triacylglycerol LML (C12C14C12) was reported recently (1). The unit cell dimensions of/T LML area--22.9A, b = 5.7A, c =66.8A, a= 90 ° ,f3= 91 ° and ), --90 °.…”
mentioning
confidence: 98%
“…For TAG of the type p.p+2.p (p even, saturated), for which β′ is the most stable polymorph, only rough structural information is known. In 1991, Birker et al (6) published a variety of structural elements of the β′-2 structure of 12.14.12, but a final structure at the atomic level could not be obtained. A summary of their findings will be given here.…”
mentioning
confidence: 99%